Static and dynamic structural monitoring of the Santa Maria of Belém church, in Lisbon - Ramos, Luís F. (2005)
The paper details two monitoring systems implemented in the main nave of Santa Maria of Belém Church of the Monastery of Jerónimos, in Lisbon. The monitoring systems are being installed to better understand the static and dynamic behavior of the structure, with the purpose of damage detection and the improvement of seismic resistance of the monument. In the paper, preliminary investigations, numerical non-linear analyses and the first dynamic modal identification analyses are described. Also the preliminary works for the monitoring systems are presented, including the points selected for observation, the discussion of the sensors technical characteristics, as well as preliminary inspection and diagnosis. The first results of the dynamic monitoring system are shown and the future developments on the systems are presented, aiming at a full integration of all adopted techniques.